Analysis of Service Quality Satisfaction of E-KTP Service at Public Administration and Civil Registration Office of Bogor District - Shafira Rizq; Moh Djemdjem Djamaludin; Yani Nurhadryani (Department of Family and Consumer Sciences, Faculty of Social and Human Ecology, IPB University, 2018)
The purpose of this study was to analyze the satisfaction of service quality in the E-KTP service of the Bogor District Population and Civil Registration Service. The design of this study was a cross-sectional study at Disdukcapil Bogor District. The method used in this study is Servqual, importance performance analysis (IPA), and customer satisfaction index (CSI) with 100 respondents selected using a convenience technique. The result of customer satisfaction index analysis shows that the community has been